Long-Term Results of Cabergoline Add-on Long-Acting Somatostatin Analogue Therapy in Acromegaly Patients - Mehmet Muhittin Yalçın; Gizem Bedir Keser; Meriç Coşkun; Afruz Babayeva; Emrah Çeltikçi; Mehmet Arda İnan; Emetullah Cindil; Aylar Poyraz; Ethem Turgay Cerit; Alev Eroğlu Altınova; Müjde Aktürk; Füsun Baloş Törüner; et al. (Gazi Medical Journal)
Objective: To investigate the efficacy of the dopamine agonist cabergoline in uncontrolled acromegaly despite long-acting somatostatin analog (SSA). Methods: Thirty-five patients with acromegaly who were followed up in the department of endocrinology and metabolism of our university were analyzed. Thirty-five patients with acromegaly who did not respond adequately to postoperative SSA and in whom cabergoline was added to the treatment were analyzed. Patients were retrospectively evaluated in terms of age, gender, insulin-like growth factor-1 (IGF-1) values before and after cabergoline, disease duration, treatment dose, adenoma size, growth hormone level, and prolactin staining on pathologic examination. Results: Seventeen (48.6%) patients were female. The median age was 46.0 (41-53) years, and the median disease age was 10 (3-43) years. Twenty-eight (80.0%) were macroadenomas, 7 (20.0%) were microadenomas, and prolactin staining was observed in 10 (27.8%) cases. The IGF-1 level was 443 (346-628) ng/mL before cabergoline treatment and 27.4% decrease in IGF-1 was observed after treatment (p<0.001). There was no correlation between IGF-1 decrease and cabergoline dose. The change in IGF-1 was not correlated with tumor size and age but was correlated with pre-cabergoline IGF-1 level (r=0.364, p=0.03). 8 (22.9%) patients went into remission with cabergoline treatment. There was no difference in age, gender, tumor size, or pre-treatment IGF-1 levels between those who went into remission with cabergoline treatment and those who did not. When these 8 patients were analyzed, it was observed that cabergoline treatment was continued throughout the follow-up period; remission was maintained in one patient by discontinuing SSA treatment, in three patients by decreasing the SSA dose, in two patients without treatment change, and in two patients by changing the SSA preparation. Conclusion: Cabergoline is used in the treatment of acromegaly due to its antiproliferative and proapoptotic effects on pituitary adenoma cells. The efficacy of cabergoline added to SSA treatment is controversial in the literature. In our study, remission was achieved in 22.9% and IGF-1 reduction was observed in 27.4% with cabergoline treatment in patients with inadequate response to SSA treatment. Cabergoline added to SSA is an effective treatment in terms of IGF-1 control. This effect may continue in the long-term.